2016
DOI: 10.1136/bmj.i1030
|View full text |Cite|
|
Sign up to set email alerts
|

Refugee migration and risk of schizophrenia and other non-affective psychoses: cohort study of 1.3 million people in Sweden

Abstract: OBJECTIVETo determine whether refugees are at elevated risk of schizophrenia and other non-affective psychotic disorders, relative to non-refugee migrants from similar regions of origin and the Swedish-born population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
200
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(224 citation statements)
references
References 34 publications
13
200
2
5
Order By: Relevance
“…In non-migrants, exposure to trauma (Schäfer & Fisher 2011), loss (Morgan et al 2007) or cumulative disadvantage (Morgan et al 2008) may increase psychotic disorder and symptoms, particularly amongst those vulnerable to psychosis (Spauwen et al 2006). Relatedly, a recent study in Sweden found refugees were 66% more likely to be diagnosed with schizophrenia than non-refugee migrants from the same region of origin (Hollander et al 2016), consistent with a role for additional traumas in the aetiological pathway. Direct evidence for such an effect, is, however, missing and should be a priority for future epidemiological research in this field.…”
Section: Main Hypothesesmentioning
confidence: 68%
See 1 more Smart Citation
“…In non-migrants, exposure to trauma (Schäfer & Fisher 2011), loss (Morgan et al 2007) or cumulative disadvantage (Morgan et al 2008) may increase psychotic disorder and symptoms, particularly amongst those vulnerable to psychosis (Spauwen et al 2006). Relatedly, a recent study in Sweden found refugees were 66% more likely to be diagnosed with schizophrenia than non-refugee migrants from the same region of origin (Hollander et al 2016), consistent with a role for additional traumas in the aetiological pathway. Direct evidence for such an effect, is, however, missing and should be a priority for future epidemiological research in this field.…”
Section: Main Hypothesesmentioning
confidence: 68%
“…Current evidence strongly refutes this possibility (Lundberg et al 2007; van der Ven et al 2015), notwithstanding the possibility that exposure to pre-migratory traumas partially increases psychosis risk in migrants (Hollander et al 2016). Experiences of trauma or social adversity may be important push factors for some migrants who choose – or are forced – to emigrate.…”
Section: Main Hypothesesmentioning
confidence: 96%
“…3 In a linked paper (doi:10.1136/bmj.i1030), Hollander and colleagues argue that this increase is due predominantly to exposure to psychosocial adversities. 4 They used national register data to carry out a cohort study of more than 1.3 million people in Sweden, in which risk of non-affective psychosis was compared not only between people born in Sweden and migrants to Sweden but also between refugees and non-refugees within the migrant group. They hypothesised that, because of their increased vulnerability to psychosocial adversity, incidence of non-affective psychosis would be particularly high in the refugee group.…”
mentioning
confidence: 99%
“…Background Many European organisations provide creative activities for displaced people, including refugees and asylum seekers, that aim to reduce social isolation and counter prevalent mental health issues including anxiety, depression, nonaffective psychosis and post-traumatic stress disorder. [1][2][3] A growing body of evidence suggests that taking part in artistic and cultural activities benefits human health and wellbeing, 4-6 though this research has been mostly non-collaborative in nature. Although creative activities are seen to provide major benefits for displaced people, researchers need to become 'increasingly conscious of the value of recording and analysing what has been happening' [ 7 p1] to make effective use of a limited service provision.…”
Section: O16mentioning
confidence: 99%